2021
DOI: 10.1002/ctm2.520
|View full text |Cite
|
Sign up to set email alerts
|

Blood small extracellular vesicles derived miRNAs to differentiate pancreatic ductal adenocarcinoma from chronic pancreatitis

Abstract: Background The differential diagnosis of pancreatic ductal adenocarcinoma (PDAC) from chronic pancreatitis (CP) is clinically challenging due to a lack of minimally invasive diagnosis methods. MicroRNAs (miRNAs) derived from small extracellular vesicles (EVs) in the blood have been reported as a promising diagnosis biomarker for various types of cancer. However, blood small EV miRNA signatures and their diagnostic value to differentiate between PDAC and CP remain to be determined. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The sensitivity and specificity of these miRNAs were higher than 80%. Several studies have been reported the deregulation of miR-142-3p ( Lv et al, 2012 ; Hu et al, 2013 ; Wang et al, 2018 ; Gao et al, 2019 ; Liu et al, 2021 ), miR-199a-5p ( Zhou et al, 2015 ; Zhang et al, 2021 ), miR-223-5p ( Gilicze et al, 2014 ; Zhu et al, 2019 ; Deng et al, 2021 ), let-7d-5p ( De Santis and Götte, 2021 ; Li et al, 2021 ), miR-148b-3p ( Mollazadeh et al, 2019 ; Yuan et al, 2019 ; Shan et al, 2021 ), miR-340-5p ( Guo et al, 2021 ; Huang et al, 2021 ; Tan et al, 2021 ), and miR-421 ( Chen et al, 2019 ; Mo et al, 2020 ) in the blood of different cancer types. The KEGG pathway analysis showed that the microRNAs in cancer and P53 signaling pathway were the most enriched pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of these miRNAs were higher than 80%. Several studies have been reported the deregulation of miR-142-3p ( Lv et al, 2012 ; Hu et al, 2013 ; Wang et al, 2018 ; Gao et al, 2019 ; Liu et al, 2021 ), miR-199a-5p ( Zhou et al, 2015 ; Zhang et al, 2021 ), miR-223-5p ( Gilicze et al, 2014 ; Zhu et al, 2019 ; Deng et al, 2021 ), let-7d-5p ( De Santis and Götte, 2021 ; Li et al, 2021 ), miR-148b-3p ( Mollazadeh et al, 2019 ; Yuan et al, 2019 ; Shan et al, 2021 ), miR-340-5p ( Guo et al, 2021 ; Huang et al, 2021 ; Tan et al, 2021 ), and miR-421 ( Chen et al, 2019 ; Mo et al, 2020 ) in the blood of different cancer types. The KEGG pathway analysis showed that the microRNAs in cancer and P53 signaling pathway were the most enriched pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian network analysis demonstrated that miR-95-3p was associated with PDAC, and miR-26b-5p was associated with pancreatitis. miR-95-3p/miR-26b-5p and its combination with CA-19-9 could separate PDAC from CP, and miR-335-5p/miR-340-5p was identified to associate with PDAC metastasis and poor prognosis [ 175 ].…”
Section: Biomarkers and Therapeutic Approachesmentioning
confidence: 99%
“…On the other hand, LB techniques, which involve collecting tissue, blood, or urine, offer a potentially more cost-effective alternative. Traditional protein markers such as CA19-9 and CEA can be detected using commercial products such as IMMray ® PanCan-d test, Galleri ® test, and CellSearch ® test, with costs ranging from USD 900 to USD 995 [ 216 , 217 , 218 ] in Table 1 .…”
Section: Market Of Pc Screening Testmentioning
confidence: 99%